Immobilization of Paclitaxel on Hydroxyapatite for Breast Cancer Investigations - Martins, Murillo L.; Pinto, Thais S. [UNESP]; Gomes, Anderson M. [UNESP]; Parra, João P. R. L. L. [UNESP]; Franchi, Gilberto C.; Zambuzzi, Willian F. [UNESP]; Rodrigues, Cloves G. (American Chemical Society (ACS), 2020)
A simple method for immobilization of the chemotherapy drug paclitaxel (PTX) on hydroxyapatite nanoparticles (n-HAP) using the biopolymer chitosan as a trapping agent is described focusing on applications involving breast cancer cells. n-HAP with two distinct crystallinity profiles were used: with predominant crystallization along the long axis and with a more homogeneous crystallization in all directions. In the first scenario, the interactions between chitosan and both the OH and PO43- groups on the surface of the nanoparticles are favored and lead to a more efficient attachment of the drug. In this case, PTX is found to remain mostly attached to the n-HAP for at least 24 h, while being dispersed in aqueous solution. During this time, the activity of the drug is inhibited as corroborated by in vitro assays with breast cancer cells. With that, the in vitro experiments revealed distinct effects from the drug-loaded nanoparticles on the cells depending on the experimental conditions. In a short term, that is, in 24 h, the cells exhibit higher viability than those challenged with nonloaded materials. Nevertheless, after 72 h, even a small content of PTX in the presence of n-HAP can reduce the cells' viability via stimulation of the apoptotic phenotype and suppression of survival stimuli.